ANALISA PENGARUH DARI CORPORATE REPUTATION PADA FINANCIAL PERFORMANCE DENGAN MENGGUNAKAN BRAND EQUITY SEBAGAI VARIABEL INTERVENING PADA SEKTOR INDUSTRI PERHOTELAN DI SURABAYA - Anthony Ananto; Sarce Elsye Hatane (Business Accounting Review, 2016)
This study aimed to know the direct affect of corporate reputation and brand equity to the financial performance of companies in the sector of the hospitality industry in the area of Surabaya. This study used the signaling theory in data collection through questionnaire that distributed to 35 hotels from 3-to-5-star hotels and using SmartPLS2 to process acquired data. The result given from the data processing was the corporate reputation and brand equity had positive and significant correlation to the financial performance of companies in the sector of the hospitality industry in the area of Surabaya. In addition the results of this study also indicated that hotel which giving the best facility and private customer practices (exclusive services) to their customers could increase the brand loyalty of customers